READING ANXIETY AND ITS EFFECT TOWARDS READING COMPREHENSION ON GRADE EIGHT STUDENTS OF SMP NEGERI 1 BAUBAU - Sri Wulandari; Faisal Islamy (English Education Journal, 2022)
Problem statement of this research was whether there are any significant correlation of reading anxiety towards reading comprehension on grade eight students of SMP Negeri 1 Baubau. Objective of the research was to find out whether there was the correlation reading anxiety towards reading comprehension on grade eight students of SMP Negeri 1 Baubau. The data collection in this research was carried out using a research instrument in the form of a questionnaire to determine the student’s reading anxiety and a test to determine student’s reading comprehension. The data obtained were analysis by descriptive statistical analysis and inferential statistical analysis. The results of this research showed that the correlation coefficient value of students reading anxiety towards students reading comprehension was 0.037 with a significant level of 0.798. Because the sig.(2-tailled) > 0.05 the hypothesis H0 is accepted and H1 was rejected. It means that there was not any significant and correlation classroom reading anxiety towards reading comprehension on grade eight students of SMP Negeri 1 Baubau.